Idiopathic Isolated Omental Panniculitis Confirmed by Percutaneous CT-Guided Biopsy (Gut and Liver, 2009)
The preoperative diagnosis of intraabdominal panniculitis is difficult due to its rarity. However, the increased use of abdominal computed tomography (CT) for a variety of indications has increased the diagnosis of intraabdominal panniculitis, including omental panniculitis. The characteristic CT features of intraabdominal panniculitis are increased attenuation of the adipose tissue, the fat-ring sign, a tumoral pseudocapsule, soft-tissue nodules, and a left-sided orientation of mass maximum transverse diameter. Recognition of these features is valuable in the diagnosis of panniculitis, and hence percutaneous CT-guided biopsy to determine their presence may prevent unwarranted surgery. We report the case of a 61-year-old man found to have an idiopathic isolated omental panniculitis that was diagnosed by abdominal CT and percutaneous CT-guided biopsy.